The Quality of Life People Living with HIV/AIDS - Khallifah, Alliyah Nur; Islamia, Intan; Adnan Reza, Faisal; Damayanti, Rika (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) is a chronic disease that attacks the human immune system and reduces the body’s ability to fight infections. This study aimed to describe the quality of life of people living with HIV/AIDS. A descriptive qualitative method was employed, with data collected through semi-structured interviews and field notes, and analyzed using NVivo 12 Plus to draw conclusions. The study involved three participants selected through purposive sampling. The findings indicate that the quality of life of people living with HIV/AIDS is shaped through a dynamic and individual adaptation process influenced by interactions among physical, psychological, social, and environmental conditions. Risk behaviors, such as unsafe sexual practices and drug use, were identified as factors contributing to HIV infection among the participants. Physically, all participants experienced weight loss, with one participant having entered the AIDS stage. Nevertheless, all participants were able to carry out daily activities and routinely adhere to antiretroviral therapy. Psychologically, participants experienced negative emotions at the initial stage of infection and gradually reached a phase of self-acceptance, with happiness interpreted through family roles, physical activities, and community involvement. Social relationships revealed limited family support, experiences of discrimination, and a desire to have a partner. The participants’ living and working environments were relatively safe, although limited access to healthcare services was reported. Each participant demonstrated different dynamics of quality of life; however, in general, they continued to strive to live their lives through gradual self-management.Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) merupakan penyakit kronis yang menyerang sistem kekebalan tubuh manusia dan menurunkan kemampuan tubuh dalam melawan infeksi. Penelitian ini bertujuan untuk menggambarkan kualitas hidup orang dengan HIV/AIDS. Metode penelitian ini menggunakan kualitatif deskriptif dengan pengumpulan data melalui wawancara semi-terstruktur dan catatan lapangan, teknik analisis data menggunakan NVivo 12 Plus untuk penarikan kesimpulan. Subjek penelitian berjumlah tiga orang yang ditentukan melalui teknik purposive sampling. Hasil penelitian menunjukkan bahwa kualitas hidup orang dengan HIV/AIDS terbentuk melalui proses adaptasi yang dinamis dan bersifat individual, dipengaruhi oleh interaksi antara kondisi fisik, psikologis, sosial, dan lingkungan. Perilaku berisiko seperti hubungan seksual tidak aman dan penggunaan narkoba menjadi faktor penyebab subjek terinfeksi. Temuan penelitian ini menunjukkan bahwa secara fisik seluruh subjek mengalami penurunan berat badan, dengan satu subjek telah memasuki fase AIDS. Namun demikian, seluruh subjek tetap menjalani aktivitas sehari-hari dan rutin dalam mengonsumsi obat antiretroviral. Subjek mengalami perasaan negatif pada awal terinfeksi dan perlahan mencapai fase penerimaan diri dengan kebahagiaan dimaknai melalui peran keluarga, aktivitas olahraga, dan keterlibatan komunitas. Hubungan sosial menunjukkan keterbatasan dukungan keluarga, pengalaman diskriminasi, serta keinginan memiliki pasangan. Lingkungan tempat tinggal dan pekerjaan subjek relatif aman, meskipun terdapat keterbatasan akses layanan kesehatan. Masing-masing subjek memiliki dinamika kualitas hidup berbeda, namun secara umum mereka tetap berupaya menjalani kehidupan disertai pengelolaan secara bertahap.